2004
DOI: 10.1111/j.1523-1755.2004.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia in erythropoietin-treated pediatric as compared to adult chronic dialysis patients

Abstract: Hemoglobin values in rHuEPO-treated pediatric dialysis patients lagged behind those of adult patients, with pediatric patients achieving target hemoglobin values only a minority of the time (45.9% and 30.5% patient years, respectively, for hemodialysis and peritoneal dialysis). Trends show recent improvement in anemia treatment of children on dialysis. Still, further attention to and analysis of rHuEPO and iron therapy in pediatric dialysis patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In this study, nearly half of children were below target, with nearly a 10th of the population having very low Hb levels, despite virtually all patients being prescribed ESAs. This finding is consistent with data from the USA, showing the prevalence of Hb levels below 11 g/dL between 33 and 54% of HD patients [2,[24][25][26] and between 31 and 70% of PD patients [2,24], and the presence of anaemia (including the use of ESA in defining anaemia) in 97% of paediatric Stage 5 CKD patients [27]. As in a US study [24], ESAs were prescribed in over 90% of dialysis children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, nearly half of children were below target, with nearly a 10th of the population having very low Hb levels, despite virtually all patients being prescribed ESAs. This finding is consistent with data from the USA, showing the prevalence of Hb levels below 11 g/dL between 33 and 54% of HD patients [2,[24][25][26] and between 31 and 70% of PD patients [2,24], and the presence of anaemia (including the use of ESA in defining anaemia) in 97% of paediatric Stage 5 CKD patients [27]. As in a US study [24], ESAs were prescribed in over 90% of dialysis children.…”
Section: Discussionsupporting
confidence: 89%
“…Anaemia is a common feature among children with endstage renal disease (ESRD) [1], due mainly to impaired erythropoietin synthesis by the diseased kidneys, and an absolute or functional iron deficiency [2]. Other contributing factors include inflammation, regular blood loss, vitamin deficiency, hyperparathyroidism, haemoglobinopathies, haemolysis, uraemia and medications [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correction of anaemia through erythropoiesis stimulation leads to decreased blood transfusion requirements and anti-HLA immunisation [2], increased appetite and tolerance to exercise [3,4] and improved school performance or quality of life [5,6]. Recombinant human erythropoietin (r-HuEPO) has become the standard of care in treating anaemia associated with chronic renal failure (CRF) in adults [7][8][9] as well as in children [10,11]. Conventional r-HuEPO requires two to three subcutaneous or intravenous injections per week over long periods of time, until successful kidney transplantation restores kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas studies have shown anemia to be considerably more prevalent among pediatric dialysis patients than among adult patients, the bulk of the research on anemia in hemodialysis (HD) patients has been conducted in adults. It is widely recognized, however, that pediatric patients who receive HD experience chronic blood loss and resultant iron deficiency (2). In fact, iron loss is expected to be even greater in smaller children than in adults because equal volumes of obligate blood loss with each dialysis session represents a larger fraction of the total iron pool.…”
mentioning
confidence: 99%